Recent HIV infection among newly diagnosed cases and associated factors in the Amhara regional state, Northern Ethiopia: HIV case surveillance data analysis (2019-2021) - Alemu, Tefera; Ayalew, Misganaw; Haile, Mahteme; Amsalu, Abraham; Ayal, Alie; Wale, Fisseha; Belay, Amogne; Desta, Birhanu; Taddege, Tesfahun; Lankir, Damtie; Bezabih, Belay (Frontiers in Public Health, 2022)
Background Distinguishing a recent from long-standing HIV infection is a critical step to reduce new infections in 2030. Therefore, this analysis determines the proportion of recent HIV infections among newly diagnosed cases and associated factors in the Amhara regional state between 2019 and 2021. Methods We got the HIV case-based surveillance dataset (July 2019 up to August 12/2021) from the Amhara Public Health Institute. Recent infection is an infection gained within the last 12 months as identified by Asante recency test kits. Logistic regression was carried out to identify factors associated with recent infection. Adjusted odd with 95% CI and a p-value of < 0.05 was considered to declare significant associations. Results Out of 5,689 eligible cases, 3,129 (55%) recency tests had been performed. The proportion of recent HIV infection is 443 (14.2%, 95% CI: 13, 15.4%). High proportion of recent infections is reported from Bahir Dar city (23.3%), Central Gondar (17.7%), West Gojjam (16.5%), North Shewa (16.5%) and South Gondar zones (15.7%). Besides, the proportion of recent infection is high among clients aged ≥ 51 years (32.4%), illicit drug users (30.6 %), homelessness (28.5%), current commercial sex workers (27.9%), prisoners (21.1%), and among clients with invasive medical procedures (22.2%). Recent infection is significantly associated with females (AOR: 1.9, 95% CI: 1.2–3.1), secondary and above education (AOR: 2.1, 95% CI: 1.3–3.4), commercial sex workers (AOR: 1.8, 95% CI: 1.2–2.7), having contact with index case (AOR: 0.5, 95% CI: 0.3–0.8) and illicit drug utilization (AOR: 3.6, 95% CI: 1.1–12.4). Conclusion In the Amhara region, the proportion of recent HIV infection is high with marked variation across sociodemographic characteristics. We identified the risk or preventive factors associated with a recent infection. Therefore, all HIV responders should target their prevention efforts toward hot spot areas and sub-populations to stop further transmission.